Theta- and Gamma-Band Activity Discriminates Face, Body and Object Perception - Bossi, Francesco; Premoli, Isabella; Pizzamiglio, Sara; Balaban, Sema; Ricciardelli, Paola; Rivolta, Davide (Frontiers in Human Neuroscience, 2020)
Face and body inversion effects (FIE and BIE) refer to a performance decrease in recognition when these stimuli are seen upside-down. The FIE and BIE are due to the disruption of configural perceptual mechanisms. The current study aimed to investigate the neurophysiological correlates of the FIE and BIE, which are still poorly understood. Neural electrical activity was recorded using a 128 channel electroencephalogram (EEG) recording system while participants were presented with faces, bodies and houses (upright and inverted). EEG data were analysed in both the time domain (event related potentials - ERPs) and the frequency domain (induced theta (5-7 Hz) and gamma (28-45 Hz) oscillations). ERPs results showed increased N170 for inverted faces and bodies (compared to the same stimuli presented in canonical position) but not for houses. Spectral analysis indicated stronger bilateral fronto-parietal theta-band synchronisation for inverted (vs. upright) faces, and left occipito-temporal and right frontal theta-band synchronisation for upright (vs. inverted) bodies. In addition, gamma-band desynchronization was observed over right occipito-temporal electrodes for inverted (vs. upright) faces only. Our findings demonstrate clear differences in the neurophysiological correlates of face and body perception. The FIE suggests disruption of feature binding processes (occipital gamma reduction for inverted faces), together with enhanced feature-based attention (fronto-parietal theta increase for inverted faces). In contrast, the BIE may suggest that structural encoding of bodies is mediated by first stages of configural processing (occipital theta).